Decision Supporting System In Selection of Online Games Players From One Team To One Esports Medan using Naïve Bayes (Case PT. Satu E-Sport) - Marina Elsera; Andhika Sulesmana; N Nurjamiyah (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Esports is present in Indonesia as an official sport in Indonesia with the appointment of PB ESI (Indonesian Esports Association) as the main organization which is recognized by the government to manage the esports ecosystem. The selection of players (athletes) is one of the determining factors in sports to achieve the goal of winning. PT. One Esports Indonesia, which is the first legal incorporated esports organization in the city of Medan, has the opportunity to join the Indonesian professional mobile legends league known as the Mobile Legends Development League (MDL). To get and determine the players who will play, so that is determined by the coach using a 7-point Likert scale. This research comes up from this background to help in the selection of players in an open and systematic way. This study uses the nave Bayes classification method to determine the role of players, i.e : Roam/Jung/Mid, XP, and Gold. In this studying to use of players from each role through the calculation of the ranking points of capable players which are the final result of a decision supporting system for coaches to be able to determine the athletes who will fight a duel